Human macrophages differentiated in the presence of vitamin D3restrict dengue virus infection and innate responses by downregulating mannose receptor expression (2023)
Background: Severe dengue disease is associated with high viral loads and overproduction of pro-inflammatory cytokines, suggesting impairment in the control of dengue virus (DENV) and the mechanisms that regulate cytokine production. Vitamin D3has been described as an important modulator of immune responses to several pathogens. Interestingly, increasing evidence has associated vitamin D with decreased DENV infection and early disease recovery, yet the molecular mechanisms whereby vitamin D reduces DENV infection are not well understood. Methods and principal findings: Macrophages represent important cell targets for DENV replication and consequently, they are key drivers of dengue disease. In this study we evaluated the effect of vitamin D3on the differentiation of monocyte-derived macrophages (MDM) and their susceptibility and cytokine response to DENV. Our data demonstrate that MDM differentiated in the presence of vitamin D3(D3-MDM) restrict DENV infection and moderate the classical inflammatory cytokine response. Mechanistically, vitamin D3-driven differentiation led to reduced surface expression of C-type lectins including the mannose receptor (MR, CD206) that is known to act as primary receptor for DENV attachment on macrophages and to trigger of immune signaling. Consequently, DENV bound less efficiently to vitamin D3-differentiated macrophages, leading to lower infection. Interestingly, IL-4 enhanced infection was reduced in D3-MDM by restriction of MR expression. Moreover, we detected moderate secretion of TNF-a, IL-1ß, and IL-10 in D3-MDM, likely due to less MR engagement during DENV infection. Conclusions/Significance: Our findings reveal a molecular mechanism by which vitamin D counteracts DENV infection and progression of severe disease, and indicates its potential relevance as a preventive or therapeutic candidate. © 2017 Arboleda Alzate et al.